The in vivo effect of a Brassica oleracea var. capitata extract on ehrlich ascites tumors of Mus musculus BALB/C mice - (:unkn) unknown (Freund Publishing House Ltd, 1999)
An extract of Brassica oleracea var. capitata juice was prepared using petroleum ether, ether, ethanol and an Al2O3 column. The healing and tumor protecting effects of this extract were tested on Ehrlich ascites (EA) solid tumors of Mus musculus BALB/C mice. Complete disappearance of the tumors was observed in 54.5% of the animals in the experimental group (n=22) which received 20 mg/day of the extract i.p. for 28 days. Regression of the tumors (27%), fixation of tumor size (4%) and an increase in tumor size (18%) were also recorded. Neither tumor size fixation nor regression was recorded in the control group which received physiological serum (0.5 ml/day). The healing effect was found to be related to the starting tumor size. The healed animals in the experimental group were followed for 6-7 months and no tumor recurrence was recorded. The protective effect of this extract on tumor formation was also tested. Experimental animals (n=35) received 20 mg/day of the extract i.p. for 20 days. Physiological serum was administered to a control group (n=30). Transplantation of solid tumors was performed on the 20th day and extract administration was discontinued. Transplantation success was recorded 20 days after transplantation. In the experimental group, only three out of 35 mice showed tumor development, whereas in the control group the number was 23 out of 35 mice. It was also observed that the extract prevented the development of liquid EA tumors. This extract was also found to be nontoxic. Brassica oleracea var. capitata had a healing effect as well as a protective effect on EA solid tumors of mice. These results are in agreement with our previous results obtained from a liquid Brassica oleracea var. acephala juice extract.
Keywords: Brassica oleracea var. capitata; Cabbage; Cancer